The Australian media's foreign news coverage of COVID-19 and its declining reportage of the Asia Pacific region. Issue 2 (1st November 2021) - Tapsell, Ross
This article examines the Australian mainstream media's foreign news coverage of the COVID-19 pandemic. It finds that the Australian mainstream media has comprehensively covered the devastation of COVID-19 in the United States and the United Kingdom, but there was scant coverage of the death toll and policy problems of countries in Australia's region, particularly in neighbouring Southeast Asia. I documented COVID-19 television coverage in the ABC's 7 p.m. news, ABC's 730 current affairs programme and three major Australian broadsheet newspapers: the Australian, the Sydney Morning Herald and the West Australian. In a global pandemic causing widespread deaths on every continent, the article shows how the Australian mainstream media's vast disparity in world coverage conveys a distorted reality of 'newsworthy' pandemic coverage, one that I argue does not reflect Australia's increasingly diverse population nor its place in the Asia Pacific region.